Effectiveness of Child To Child Approach on Practice of Hand Washing Among School Children in a Selected School at Mangalore - Mathew, Smitha Mariam; R., Sujatha (Journal of Health and Allied Sciences NU, 2018)
Objective: Effectiveness of child to child approach on practice of hand washing.Design: Quantitative evaluative research approach & pre experimental - One group pre-test post-test design was used.Setting: This study was conducted in a selected rural school (Aided higher primary school, Pavoor- Harekala) at Mangalore.Participants: The populations covered were school children in the age group 9-10 years who met the inclusion criteria and studying in a rural school at Mangalore. 75 students from Aided higher primary school within the age 9-10 years and studying in 4th to 5th class were selected by using purposive sampling.Main outcome measures: Main outcome measure was whether the school children are able to practice the hand washing technique. Data collection was collected by using Demographic proforma and Checklist (to assess the practice of hand washing).Results: Data was analyzed using descriptive and inferential statistics. The mean post-test score on hand washing of group 1 (12.46) and group 2 (12.05) was higher as compared with pre-test score of group I (12.46) and group II (12.05) and the “p” value is <0.05. So the child to child approach was effective to teach the children hand washing technique. There was no association between the selected demographic variables and pre-test hand washing scoresConclusions: This study concludes that through proper training and motivation by peer group, that is child to child approach was an effective method to teach the children healthy habits like hand washing and other common issues concerning children.
Keywords: Child to child approach; Hand washing